Flood Inundation Mapping of Bagmati River and Impact Assessment on Building Infrastructures on Terai Plains of Nepal - Nepal, Sushanta; G.C., Kaushal Chandra (Journal of Advanced College of Engineering and Management, 2024)
Starting from the northern hills of Kathmandu Valley, the Bagmati River flows through the Mahabharat and Siwalik ranges and discharges at Padherodovan into the Terai region of Nepal. The river poses a flood hazard in the downstream areas, especially during the monsoon season. This study is about mapping flood inundation in a 2D unsteady flow simulation model using HEC RAS. The study was conducted on ~16 km stretches of the Bagmati River in Bagmati Municipality of Sarlahi district. River discharge values for various return intervals were calculated using instantaneous discharges, and probable floods of 2, 5, 10, 25, 50, and 100-year return periods were simulated for developing flood inundation maps. Flood inundation maps depict varying depths during different return periods, offering insights into the fluctuation of flood depth across the floodplain with increasing discharge. During a 100-year return period flood, which was almost equivalent to the flood of 1993, around 5061 buildings were affected, while during a 5-year return period flood, around 2511 buildings were affected. This study provides essential data for understanding flood patterns, aiding in land use zoning and flood risk mitigation for risk informed development along the Bagmati River.